Fundamental Design Issues for the Future Internet (International Journal of Engineering and Computer Science, 2013)
The need for the internet has increased multifold in the recent past. There are a lot of algorithms and techniques designed and develop for increasing the speed of the data over the internet. The routers which routes the packets to the destination also play an important role in the speedy and effective data transfer over the internet. The normal internet routers use the shortest path routing techniques for speeding over the internet. The shortest path algorithm is an effective algorithm always but a tedious situation arises when shortest path is already busy with the data and if there is heavy traffic in the shortest path. If we are sending our data through the same shortest path again the traffic will increase and again there is congestion and packet collision in the same path. Here we design a new technique which senses traffic in the network and sends the packets through the path which has the least traffic. This method prevents the path from getting further congested and reduces the packet collision.